Atributos do solo e desempenho da cultura do milho sob diferentes alturas de massa de forragem pós-pastejo - Pizzani, Rodrigo (2012)
The Crop-Livestock System (ILP) refers to an association between two activities in the same area at different periods of the year, that involves annual crops and livestock. This study aimed to: (a) evaluate the dry matter yield and residual dry matter remaining of winter intercrop forage (oat, rye and vetch) under different heights of post-grazing residue, (b) compare the productivity of maize under different crop heights of post-grazing residue and (c) examine the changes in soil properties that may be caused by cattle during the growing season of corn. The experiment was conducted in the city of Mata - RS, on a commercial farm during the agricultural period of 2009/2010 and 2010/2011, in an Ultisol. The experimental design was a randomized block design using four heights of post-grazing residues: conventional grazing (PC), with an area of 500 m2, in which there was no control of movement of animals and tall forage during the grazing; residue height of 0.10 m (M-10), 0.20 m (M- 20), 0.30 m (M-30) and an area not grazed (SP). To meet the proposed objectives, the work was divided into three parts. The first part was performed by evaluating during two periods of each crop year, soil bulk density, microporosity, macroporosity and total porosity at depths of 0.0 to 0.025, 0.025 to 0.05, 0.05-0.10 and 0.10-0.15 m, the rate of water infiltration in soil, soil resistance to penetration, phosphorus, potassium and soil organic matter. When managed correctly, the presence of animals in pasture areas will not negatively effect soil physical and chemical properties. After the grazing cycle, changes in soil physical properties were minimal and did not affect the rate of infiltration of ground water and soil resistance to penetration. The levels of soil organic matter remained in progression for the two years of assessment in both layers evaluated. Values for phosphorus and potassium decreased in every layer over the sample period. In the second part of the study were evaluated agronomic and yield components of maize. The high mass post-grazing residue in 2009/2010 did not affect dry matter yield of corn, but was not repeated in 2010/2011 due to low water availability in the region. The yield components of corn MMG and NGE were negatively influenced by the different heights of residue post-grazing in years of low water availability. The lower heights of post-grazing residue (M-10 and PC) did not provide the optimal intake of straw to the SILP-PD for subsequent crops. In the third part of the work, attributes were evaluated related to pasture (plant height, forage mass and final mass of available forage) and the dynamics of forage production in pasture of oat (Avena strigosa Schreb.), ryegrass (Lolium multiflorum Lam.) and vetch (Vicia villosa L.) managed at different heights of postgrazing residue. The objective of this part was to identify the best height of forage for aerial biomass, the effect of grazing on the mass and the rate of decomposition of winter forages after different heights of forage after grazing. The different heights of residue post-grazing may have limitations in the final mass of forage, and the treatments M-20 and M-30 were ideal for the realization of direct seeding in grazed areas.